The Implementation of a Web-Based Library Management Information System Using Barcodes at Al-Islam Vocational High School Surakarta: A Research and Development (R&D) Approach - Wijaya, Reza Dani; Rozaq Rais, Nendy Akbar; Rokhmah, Siti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study discusses the implementation of a web-based Library Management Information System utilizing barcode technology at Al-Islam Vocational High School in Surakarta. The system was developed to enhance efficiency in managing book data as well as borrowing and returning transactions in a digital environment. Built using the Laravel framework, the system ensures structured and secure web application development. The Research and Development (R&D) method was applied through stages of needs analysis, system design, development, validation, and evaluation. The implementation results indicate that the system accelerates library services, minimizes data entry errors, and facilitates user access to collection information and transaction history. Testing was conducted by involving librarians as the primary users, and evaluation results revealed a high level of satisfaction regarding the system’s ease of use and functionality. In conclusion, the system functions effectively and can serve as an efficient and user-friendly solution for digital library management in educational institutions.